The DNA Damage Inducible SOS Response Is a Key Player in the Generation of Bacterial Persister Cells and Population Wide Tolerance - Podlesek, Zdravko; Žgur Bertok, Darja (Frontiers in Microbiology, 2020)
Population-wide tolerance and persisters enable susceptible bacterial cells to endure hostile environments, including antimicrobial exposure. The SOS response can play a significant role in the generation of persister cells, population-wide tolerance, and shielding. The SOS pathway is an inducible DNA damage repair system that is also pivotal for bacterial adaptation, pathogenesis, and diversification. In addition to the two key SOS regulators, LexA and RecA, some other stressors and stress responses can control SOS factors. Bacteria are exposed to DNA-damaging agents and other environmental and intracellular factors, including cigarette smoke, that trigger the SOS response at a number of sites within the host. The Escherichia coli TisB/IstR module is as yet the only known SOS-regulated toxin–antitoxin module involved in persister formation. Nevertheless, the SOS response plays a key role in the formation of biofilms that are highly recalcitrant to antimicrobials and can be abundant in persisters. Furthermore, the dynamic biofilm environment generates DNA-damaging factors that trigger the SOS response within the biofilm, fueling bacterial adaptation and diversification. This review highlights the SOS response in relation to antimicrobial recalcitrance to antimicrobials in four clinically significant species, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Mycobacterium tuberculosis.